(untitled) (Journal of Tourism & Adventure, 2022)
Everyone in the world is Buddhist because every heart has love, peace, and compassion. This is a study to find out the gap in knowledge between Buddhism and tourism. Buddhism pursues happiness by using knowledge and practice to achieve mental equanimity. In Buddhism, equanimity, or peace of mind, is achieved by detaching oneself from the cycle of craving that produces suffering and travelling broadens horizons and provides patience. It relieves stress and unwinds the mind to develop tolerance and empathy. Travelling helps to discover self. It helps to be open-minded, offers break from routine life, and provides patience. It relieves stress and unwinds the mind. It discovers human strengths and weaknesses. This article examines the social connectivity between Buddhism and tourism in Nepal. Methodologically, it is desk based qualitative study. It is a general review of Buddhism and tourism. The study finds a Buddhist worldview, plays a significant role in shaping attitudes toward Buddhist tourism.